Definition of the linearity loss of the surface temperature in static tensile tests - A. Risitano; G. Fargione; E. Guglielmino (Fracture and Structural Integrity)
Static tensile tests on material for mechanical constructions have pointed out the linearity loss of the surface temperature with the application of load. This phenomenon is due to the heat generation caused by the local microplasticizations which carry the material to deviate from its completely thermoelastic behavior,. The identification of the static load which determines the loss of linearity of the temperature under stress, becomes extremely important to define a first dynamic characterization of the material. The temperature variations that can be recorded during the static test are often very limited (a few tenths of degree for every 100 MPa in steels) and they require the use of special sensors able to measure very low temperature variations. The experience acquired in such analysis highlighted that, dealing with highly accurate sensors or with particular materials, the identification of the first linearity loss (often by eye) in the temperature curves, can be influenced by the sensibility of the investigator himself and can lead to incorrect estimates. The aim of this work is to validate the above mentioned observations on different steels, by applying the autocorrelation function to the data collected during the application of a static load. This, in order to make the results of the thermal analysis free from the sensitivity of the operator and to make the results as objective as possible, for defining the closest time of the linearity loss in the temperature-time function.